Acute post-renal kidney graft dysfunction due to cytomegalovirus-positive nephrogenic adenoma—case report and review of the literature - Hosek, Nicola; Montani, Matteo; Mani, Laila-Yasmin (Frontiers in Medicine, 2024)
Tissue-invasive cytomegalovirus (CMV) disease represents a well-recognized complication after kidney transplantation. However, direct involvement of the urogenital tract and CMV-ureteritis occur less frequently. Nephrogenic adenomas are benign lesions of the urinary tract preferentially reported in kidney transplant recipients. We herein report a second case of a 33-year-old male kidney transplant recipient with acute post-renal allograft dysfunction due to CMV-positive ureteral nephrogenic adenoma. A causal connection might be suspected but remains to be proven.